Non‐destructive, whole‐plant phenotyping reveals dynamic changes in water use efficiency, photosynthesis, and rhizosphere acidification of sorghum accessions under osmotic stress - Daniel N. Ginzburg; Jack A. Cox; Seung Y. Rhee (Plant Direct)
Abstract Noninvasive phenotyping can quantify dynamic plant growth processes at higher temporal resolution than destructive phenotyping and can reveal phenomena that would be missed by end‐point analysis alone. Additionally, whole‐plant phenotyping can identify growth conditions that are optimal for both above‐ and below‐ground tissues. However, noninvasive, whole‐plant phenotyping approaches available today are generally expensive, complex, and non‐modular. We developed a low‐cost and versatile approach to noninvasively measure whole‐plant physiology over time by growing plants in isolated hydroponic chambers. We demonstrate the versatility of our approach by measuring whole‐plant biomass accumulation, water use, and water use efficiency every two days on unstressed and osmotically stressed sorghum accessions. We identified relationships between root zone acidification and photosynthesis on whole‐plant water use efficiency over time. Our system can be implemented using cheap, basic components, requires no specific technical expertise, and should be suitable for any non‐aquatic vascular plant species.